Comparative Strength Analysis of Normal Weight and Palm Kernel Shell Reinforced Concrete Beams for Sustainable Development - Olanitori, Lekan Makanju; Okusami, Jeremiah Ibukun (European Journal of Sustainable Development, 2019)
Reduction in self-weight of Palm Kernel Shell Concrete (PKSC) over Normal Weight Concrete (NWC), reduces the amount of cement needed for construction, this is accompanied by reduction in CO2 emission associated with the production of cement: This will have reduction effect on the greenhouse, a major cause of climate change. This study carries out the comparative analysis of the strength characteristics of NWC and PKSC beams produced from four concrete mixes of 0%, 20%, 40% and 60% partial replacement of crushed granite by palm kernel shell (PKS). From each concrete mix, two beams were cast: one with shear reinforcement of 200mm spacing, while the other one without shear reinforcement, making total of eight beams. From the study, the PKS concrete beams were 3.6%, 11.24% and 15.64% lighter than the NWC beams for 20%, 40% and 60% partial PKS replacement. The study shows that reinforced concrete beams produced from 20% and 40% partial replacement of crushed aggregate by PKS have the potential of being used for structural purposes in low cost buildings. Keywords: Palm Kernel Shell Concrete, Normal weight concrete, Palm kernel shell, Strength characteristic, Cement.